OPEC ve petrol fiyatlarının artışı (1973-1979) - Aksu, Erdal (Fen Bilimleri Enstitüsü, 1992)
1950'de dünya enerji talebinin. % 27'si petrolle karşılanıyordu. 1973'de ise bu oran düzenli olarak artarak % 53 oldu. Günümüzde petrol, dünya enerji talebinin karşılanmasında enerji kaynakları içinde birinci sırayı almaktadır. Gelişmiş ülkeler petrol rezervleri bakımından yeterince zengin değilken, petrol yatakları gelişmekte olan ülkelerde, özellikle ortadoğu ülkelerinde daha zengin olarak bulunmuştur. Ortadoğu ülkelerinde üretim yapan kuyu sayıları, gelişmiş ülkelerinkinden az olduğu halde kuyu verimlerinin fazla olması nedeniyle daha çok miktarda petrol üretimi yapmaktadırlar. Batı Avrupa ülkeleri ve Kuzey Amerikadaki petrol rezervlerinin ömürleri 10-15 yıl arasında değişirken ortadoğu ülkelerindeki petrol rezervlerinin 100 yıllık üretimi karşılayacak potansiyele sahip olduğu tahmin edilmektedir. Dünya petrol ihracatının % 80'inden fazlası petrol ihraç eden azgelişmiş ülkelerden, gelişmiş ülkelere olmaktadır. İkinci dünya savaşından beri, petrol taşımacılığı yapan bu petrol tankerlerinin en önemli rotası, ortadoğudan genellikle Süveyş kanalından geçerek batıda Avrupa, doğuda Japonya'ya yine kuzey ve batı Afrika'dan Libya, Cezayir ve Nijerya petrollerini taşıyarak Avrupa' ya götüren yol olmuştur. Petrol üreticisi OPEC'e üye olan ülkeler, Venizuela dışında asıl petrol gelirlerini hampetrol ihraç ederek kazanmaktadırlar. OPEC üyesi ülkelerin rafineri kapasiteleri,gelişmiş ülkelerle karşılaştırıldığında oldukça azdır. Bununla birlikte bu ülkeler 1980 ile 1990 yılları arasında yabancı ülkelerdeki rafineri yatırımlarını önemli ölçüde artırdılar. Yedi OPEC üyesi ülkenin 1991 yılı verilerine göre, toplam kapasiteleri günde 3.6 milyon varil olan 26 yabancı rafineride ortaklıkları bulun¬ maktadır. OPEC'in aldığı kararlar sonucunda, petrol üreticisi ülkeler 1973 ve 1979 yıllarında petrol fiyatlarını artırdılar; bu durun gelişmiş ülkelerin içinde bulundukları ekonomik durgunluğu dahada artırarak, oldukça büyük miktarlardaki mali fazlanın OPEC'e üye ülkelerin elinde toplanmasına neden olmuştur. Gelişmekte olan ülkeler petrol fiyatlarının artışında en fazla etkilenen ülkeler olmuşlardır.

in 1950's 27 % af the uorld's energy demajıd uıere... meet by petraleum. This percentag.e has increased steadly and reached 53% in 1973. Nouıadays, petroleum is the nıost important fuel ta meet the uarld's energy <. dem.and. The distributian af petraleum ali över the uıorld shams sarae differences fram ane regian ta anather. üJhile same af the devaleped cauntries dan't have sufficient petraleum reservairs, some ather under develaped ar developing cauntries, especially middle east cauntries have the richest uıarld's patraleum resevairs, meeting 50% af the luorlds petraleum demand, it is claimed that uhile the petraleum resevairs in the ujest Eurape cauntries and the U.S.A are expected ta be exhausted.in 10 ar is years, the petralaum reservairs in the middle east regian uül have been exhausted far 100 years. Seme of the develaped ; : cauntries have the pauıer af marketing refining and extracting of petraleum by means af their giant petroleum campanies, producing B0% of the uorld's petîbleum demand. The middle east cauntries have the tuıa thirds af the uıarld's reservairs af petraleum. Therefare, the petraleum reservairs in the middle east cauntries have the strategical importance far the develaped cauntries, in order ta survive their indutries. Only Saudi Arabia, Kuuıait and Iraq have the 40% of the knoun uıorld's petraleum reservairs. Espeçi.ally, organizatian of petraleum exporting cauntries (OPEC) canstituted by mast af the middle east cauntries are exporting a big portion of petroleum they produce ta the develaped countries.in 1991 the net expart of OPEC mas 20.k million barrel in a day. vıı Över 80% of uorld oil exparts mave betuısen the ail-exparting underdeveloped cauntries and the develaped cauntries. As a result, since Uorld lıJar II the most important tanker routes go from the Middle East Idest ta Eurape (generally through the Suez Canal) and east to Oapan; from the Caribbean (Venezuela) north to the United States and east to Europe; and incereasingly. from North and Uest Africa ta Idestern Eurape (ca.rrying Libyan, Algena and Nigerian Crude oil). Because of its stratecigal location, the North Africa became öne of the important region af petraleum trade. 1 Petroleum producer countries uıhich are members of OPEC, ather than Venezuela, get.. mast af their petroleum incames exporting crude petraleum. Refinery capacity of the countries uhich members af OPEC is small compared to that of the developed ones. ülhile U.S.A, Canada and the other developed uestern countries produce 22.6 % af the uıorld's petraleum demgnd, they have ^1.8 % af the uorld's refinery capacity. On the other hand, uıhile the middle east cauntries praduce 27 % af the uarld's petraleum demand, they can only pracess 1% of the total ıuarld praduct.in the years betueen 1980 and 1990, the OPEC cauntries increased their investment far refinery constructian in the fareign cauntries. According ta the 1991 recardings 7 cauntries uhich are members of OPEC, they have 26 companies having a daily capacity af 3.6 millian barrels in fareign cauntries, in additian ta this, they are providing 2 millian barrels crude petraleum, daily,for these refineries. The petroleum producer cauntries increased the price af petraleum in 1973 and 1979. As a result af this, develaped cauntries gave the priority far alternative energy usage and reduced their energy consumption. The increased petraleum prices caused the trade rates to reduce and as a result of this the incames of the developed cauntries reduced. From the OECD ta the OPEC a big amount of money has been trans- fered for the petraleum imported. The increase in the petroleum prices caused the.economical situation,uıhich uıas already in bad condition, ta became uorse. Because the OPEC couldn't spend the maney they gat fram the petroleura, they invested a big partion af this maney ta the banks in fareign cauntries, in 1980, the excess amaunt af maney OPEC had uas 3A-5 billian dallar. vııı Develaping countries have been effected by the increased petroleum prices more, compared ta the dev.eloped anes. As a result af these incerases in the petroleum prices, the rate af grauıth af the OECD have declined. Therefore OECD reduced the demands af buying gaads fram the developing cauntries. Related ta this situatian the price af the goads, uıhich develaping - cauntries exporting, reducedî in additian ta this develaping cauntries uıere paying big amount af maney ta impart gaads. in the years 1973 and 1974 the amount paid far petraleum has increased by 16 billion dallars. in the years betuıeen 1978 and 1980 this increase uıas 25 billian dallars. The U.S.A. lost its economical pouıer in the early 1970's and the demand for dallar decreased. Therefare. the surplus af dallar has been experi enced ali över the uıorld. The crisis of petraleunı experienced at this time. As a result of this the cauntries meeting a financial deficit increased their demands far dallar. This situatian tuas advantag^ous far the U.S.'A. There¬ fare it uıas considered that the U.S.A may have planed this crises ar at least the U.S.A kneuı that this crisis uıoüld happen. The U.S.A had the pouıer of contralling middle east petraleum palitically in the 1970's..The events starting the invation of Kuuıait by Iraq and trade embargo applied ta Iraq far getting it aut af Kuuıait has ended by the gulf uıar. The Uictary, by the allied farces gave the U.S.A a big pouıer aver the middle east petroleum. This is a very good example uıhich shouıs ] that the U.S.A. has the control of middle east petraleumJ physicaly as ueely as paliticaly it had in the 1970's. Although Turkey has enough amount af refiniry capacites in order ta meet its damestic demand, since its sources af ccude petroleum is not rich enaugh,, it is depended ta the impart petraleum»in 1990, Turkey's irnpart af petraleum uıas 20 millian tan and the cost of this amaunt uıas 3393.8 million dallar. Depending on the increase in the petroleum prices, the amount paid by Turkey uıill be incrased. Petraleum uıill maintain it's key position in the uıorlrf economy by the year coming decade. The tuıo big petraleum crisis experienced in 1973 and 1979 are ix not considered as a danger nowadays. Today there are several technigues to store petroleum. The amounts rof the stocks can meet the petroleum demands of OECD for 60 to 90 days. The improvement in the petroleum extracting methods is another factor preventing the world from new crisis The improvement which the U.S. A provided extract pet*:-: roleum, and the discoveries in the former Soviet Union especially in Siberra and North Sea, new reservoirs found in the developing countries rescued world to be dependent :-to DPEC. Moreover developed countries have found new techniques in order to use alternative energy sources since 1970. Because economical situation of all the OPEC members depend petroleum, it is very difficult to follow a policy which tends to increase petroleum prices. It is nece' sary to reduce production in order to rise the price of petroleum. This situatiq.n causes the mentioned count ries not to get enough income from petroleum. The new relations of OPEC with giant international petroleum companies are the important developments shown in the petroleum market. A new dimension has been added to petroleum market by the national companies and big petroleum companies in the areas of investment of refinery and distribution of petroleum. This relationship is useful for both sides. Big petroleum companies are seeking new long lasting petroleum reservoirs since the reservoirs in their home countries don't "have long lasting life. OPEC need financial support and technology in order to extract and process the crude petroleum. Today the benefits of the petroleum producer countries and the petroleum consumer countries are not conflict each other. Because the petroleum is very restricted, the bad use of the reservoirs will create a bad situation for both sides. The increase of petroleum prices, like in the 1970's, effect the under developed and developing countries.
OPEC and the rise of petroleum prices(1973-1979)
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1992
Keywords: Petrol ve Doğal Gaz Mühendisliği; Fiyat artışı; OPEC; Petrol; Türkiye; Petroleum and Natural Gas Engineering; Price inerease; Organization of the Petroleum Exporting Countries; Petroleum; Turkey